Synthesis, physical studies and crystal structure determination of Y(III) and Er(III) complexes of 1-(pyridin-2-yl)-2-(pyridine-2-ylmethylene)hydrazine - Gueye, Mbosse Ndiaye; Dieng, Moussa; Lo, Djiby; Thiam, Ibrahima Elhadji; Barry, Aliou Hamady; Gaye, Mohamed; Sall, Abdou Salam; Retailleau, Pascal (European Journal of Chemistry, 2017)
Two isotype mononuclear yttrium(III) and erbium(III) complexes, {[Y(HL)(OAc)2(H2O)2]. (H2O)∙(NO3)} (1) and {[Er(HL) (OAc)2(H2O)2].(H2O)∙(NO3)} (2), where HL is the neutral Schiff base ligand 1-(pyridin-2-yl)-2-(pyridine-2-ylmethylene)hydrazine, and OAc is the acetate anion, have been synthesized and characterized by physicochemical methods and single crystal X-ray determination. Both complexes crystallizes in the triclinic space group Pī with unit cell dimensions for complex of Y(III) a = 7.909 (2) Å, b = 11.718 (4) Å, c = 12.497 (3) Å, α = 78.907 (3)°, b = 73.840 (3)°, γ = 72.074 (3)°, V = 1051.26 (6) Å3, Z = 2, R1 = 0.051 and wR2 = 0.112 and for complex of Er(III)a = 7.913 (1) Å, b = 11.719 (2) Å, c = 12.487 (2) Å, α = 78.832 (1)°, α = 73.674 (1)°, γ = 72.012 (1)°, V = 1049.64 (3) Å3, Z = 2, R1 = 0.028, and wR2 = 0.062. In both complexes, the coordination polyhedra around Ln(III) atoms are best described as a distorted tricapped trigonal prism. Antioxidant activities of the ligand and its Y(III) and Er(III) complexes are studied.